Neodymium-iron-boron magnet and preparation method and application thereof

By designing structures of easy demagnetization, non-easy demagnetization and bonding areas in NdFeB magnets, and using glue to bond magnets, the problem of insufficient anti-demagnetization performance of existing NdFeB magnets at high temperatures is solved, and cost reduction and performance improvement are achieved.

CN119601329APending Publication Date: 2025-03-11FUJIAN CHANGTING GOLDEN DRAGON RARE EARTH CO LTD

Patent Information

Application Number
CN202311125207.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing neodymium iron boron magnets have insufficient anti-demagnetization performance at high temperatures, and the heavy rare earth resources are scarce, resulting in high costs.

Method used

By designing structures of easy demagnetization, non-easy demagnetization and bonding areas in neodymium iron boron magnets, the magnets are bonded with glue to reduce the use of heavy rare earths, and the coercive force and thermal stability of the magnets are improved through specific magnet components and process treatments.

Benefits of technology

It realizes that while reducing the use of heavy rare earths, maintains good anti-demagnetization performance, reduces the cost of magnets, and improves the durability of magnets at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601329A_ABST
    Figure CN119601329A_ABST
Patent Text Reader

Abstract

The invention discloses a neodymium-iron-boron magnet and a preparation method and application thereof. The neodymium-iron-boron magnet comprises an easy-to-demagnetize area, a non-easy-to-demagnetize area and a bonding area, and the volume of the easy-to-demagnetize area accounts for 15%-50% of the total volume of the neodymium-iron-boron magnet; wherein the volume of the bonding area accounts for 0.5%-4.0% of the total volume of the neodymium-iron-boron magnet; wherein the ratio of the coercive force of the non-easy demagnetization area to the coercive force of the easy demagnetization area is 0.7-1. According to the neodymium-iron-boron magnet provided by the invention, the cost can be greatly reduced, and meanwhile, good demagnetization resistance is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a neodymium iron boron magnet and a preparation method and application thereof. Background Art

[0002] Since its introduction, NdFeB permanent magnet materials have been widely used in the fields of automobiles, wind power, home appliances, industrial robots, etc. Due to the different working conditions in various fields, the performance requirements of magnetic steel for products in their fields are also different. In recent years, new energy vehicles have flourished, and the demand for magnetic steel in the main drive motor has increased sharply. Since the normal operating temperature of the main drive motor is mainly concentrated in the range of 120-180°C, NdFeB requires higher coercivity and thermal stability. In order to improve the temperature resistance of rare earth permanent magnets, a large amount of heavy rare earths Dy and Tb are usually added to increase the main phase magnetocrystalline anisotropy field. However, the scarcity of heavy rare earth resources and high prices have seriously restricted the application of NdFeB magnets in various industries.

[0003] With the increasing demand for high-performance magnets, grain boundary diffusion technology has gradually become known and accepted by everyone. Conventional grain boundary diffusion technology uses a physical vapor deposition method to deposit the diffusion source on the surface of the magnet and then penetrate the diffusion source into the interior of the magnet along the grain boundary under high temperature and a certain pressure. The biggest advantage of this technology is that it can greatly improve the coercive force by using only a small amount of heavy rare earth while keeping its remanence almost unchanged. In terms of the effective utilization rate of heavy rare earth, traditional grain boundary diffusion products have been greatly improved compared with non-grain boundary diffusion products.

[0004] However, since the reverse magnetic field generated after the coil in the motor is energized is not a uniform magnetic field, the position of the magnet close to the coil is most susceptible to demagnetization and is called the easy demagnetization zone, and the position far away from the coil is not easily demagnetized and is called the non-easy demagnetization zone. In NdFeB magnets, in addition to being subjected to the demagnetization field of the magnetic circuit during operation, the magnets must also be subjected to demagnetization caused by rising temperature. In the magnetic circuit, the demagnetization of the magnets starts from the corners, while the demagnetization caused by the increase in operating temperature starts from the core. In order to solve the demagnetization of the core at high temperatures, Chinese patent CN111653407A discloses a gradient-distributed NdFeB magnet, which performs different grain boundary diffusion treatments on different regions of the NdFeB magnet to reduce the demagnetization rate at high temperatures. However, it is processed in different regions of the entire magnet, which is extremely difficult to operate, and the anti-demagnetization performance is still not ideal. Summary of the invention

[0005] In order to overcome the defect of demagnetization of NdFeB magnets in the prior art, the present invention provides NdFeB magnets and a preparation method and application thereof. The NdFeB magnets provided by the present invention can achieve good anti-demagnetization performance while significantly reducing costs.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] The present invention provides a NdFeB magnet, which comprises an easily demagnetized area, a non-easy demagnetized area and a bonding area, wherein the volume of the easily demagnetized area accounts for 15%-50% of the total volume of the NdFeB magnet;

[0008] Wherein, the volume of the bonding area accounts for 0.5%-4.0% of the total volume of the NdFeB magnet;

[0009] Wherein, the ratio of the coercive force of the non-demagnetizable region to the coercive force of the demagnetizable region is 0.7-1.

[0010] In the present invention, the volume of the easily demagnetized area accounts for 25%-50% of the total volume of the NdFeB magnet, for example, 32% or 50%. The volume of the easily demagnetized area within the scope of the present invention is more conducive to the stable performance of the NdFeB magnet and the accurate utilization of the heavy rare earth Dy\Tb, and can also reduce eddy current loss to a certain extent.

[0011] In the present invention, the ratio of the coercive force of the non-demagnetized region to the coercive force of the demagnetized region may be 0.87-0.96, preferably 0.90-0.95, such as 0.90, 0.92 or 0.93.

[0012] In the present invention, the material of the bonding area can be a substance that can bond the easily demagnetized area and the non-easy demagnetized area without affecting the performance of the NdFeB magnet, preferably glue, and the glue is more preferably one or more of resin glue, polyester glue and hot melt glue.

[0013] Since the magnetic steel is usually in the motor slot, the heat dissipation condition is not good. During the operation of the motor, it is easy to generate relatively high eddy current loss on the magnetic material, resulting in an increase in the surface temperature of the magnet. When the temperature exceeds its working temperature, it is easy to cause the magnet to demagnetize. The magnets of the present invention are bonded with glue to produce insulation between the magnetic steels, which increases the resistance between the magnetic steels to a certain extent. Moreover, the glue does not have magnetic properties, so there is no demagnetization, which is beneficial to reduce the eddy current loss of the magnetic steel at high temperature and enhance the temperature resistance and anti-demagnetization ability of the magnetic steel. The present invention is different from a whole magnet or a conventional bonded magnet. On the one hand, the magnetic properties of the magnetic steel can be flexibly customized and strengthened according to the easy demagnetization area of ​​the magnetic steel in the motor. On the other hand, during use, the non-easy demagnetization area is subjected to a smaller reverse field and temperature than the easy demagnetization area, which means that the actual coercive force performance requirement of the non-easy demagnetization area is less than that of the easy demagnetization area. Therefore, the amount of heavy rare earth can be saved by lowering the coercive force, and the purpose of reducing costs is finally achieved. In addition, the anti-demagnetization ability of the whole non-bonded magnetic steel in the motor is equivalent.

[0014] In the present invention, the volume of the bonding area may be 1%-4%, where the percentage is the percentage of the volume of the bonding area to the total volume of the NdFeB magnet.

[0015] In the present invention, the width of the bonding area can be 0-0.12mm, but not 0; preferably 0.05mm-0.12mm. The width of the bonding area mainly affects the magnetic flux of the magnet. The wider the width, the larger the volume proportion of the bonding area. Under the same volume, the proportion of magnetic steel will decrease, resulting in a decrease in the overall magnetic flux. Therefore, the width of the bonding area should be within the scope of the present invention, so that the magnet as a whole has a good effect.

[0016] In the present invention, the bonding area preferably has a porosity of 0%; if the glue is not applied evenly or bubbles are generated in the gaps, resulting in direct contact between the magnets, the anti-eddy current loss effect and the bonding strength will be reduced, affecting the anti-demagnetization effect. In some specific implementations, fully automatic equipment is used for magnetic steel bonding, and the glue is quantitatively and evenly applied to the bonding surface of the magnet through a nozzle, and then automatic bonding is performed on the same marble reference surface, and the glue application area is scanned by infrared, and the magnets that are not applied to the entire area are automatically identified to ensure that the bonding area of ​​the magnet has no pores and good consistency.

[0017] In the present invention, the remanence of the easily demagnetized area and the non-easy demagnetized area may be the same, and the same remanence should be understood as the remanence being the same within a certain deviation range, and the deviation may be ±0.5 kGs.

[0018] In the present invention, the difference ΔHcj between the coercivity of the non-demagnetizable region and the coercivity of the demagnetizable region may be 1 kOe-7.5 kOe, preferably 1 kOe-3 kOe, such as 1.8 kOe, 2.2 kOe, 2.4 kOe or 2.6 kOe.

[0019] The present invention also provides a method for preparing a NdFeB magnet, the steps of which include bonding a first magnet and a second magnet to obtain the NdFeB magnet;

[0020] Wherein, the first magnet forms an easily demagnetized area; the second magnet forms a non-easy demagnetized area; and the bonding forms a bonding area;

[0021] Wherein, the volume of the easily demagnetized area accounts for 15%-50% of the total volume of the NdFeB magnet;

[0022] Wherein, the volume of the bonding area accounts for 0.5%-4.0% of the total volume of the NdFeB magnet;

[0023] Wherein, the ratio of the coercive force of the non-demagnetization region to the coercive force of the demagnetization region is 0.7-1.

[0024] In the present invention, the first magnets are preferably symmetrically distributed on both sides of the second magnet.

[0025] In the present invention, the easily demagnetized area may include at least two first magnets, for example, two first magnets.

[0026] In the present invention, the percentage of the volume of the bonding area to the volume of the easily demagnetized area may be 1-5%, preferably 1.58%-3.79%.

[0027] In the present invention, the non-demagnetizable region may include 1-3 pieces of second magnets, for example, 1 piece or 2 pieces.

[0028] In the present invention, the percentage of the volume of the bonding area to the volume of the non-demagnetizable area may be 1-4%, preferably 1.58%-3.79%.

[0029] In the present invention, the volume of the bonding area refers to the sum of the volumes of the bonding area between the first magnet and the first magnet and the bonding area between the first magnet and the second magnet. In the present invention, the width of the bonding area can be 0-0.12mm, but not 0; preferably 0.05mm-0.12mm.

[0030] In the present invention, the preparation method of the first magnet and the second magnet can be a conventional method in the art, preferably, the NdFeB substrate is processed; the processing method includes one or more of a single alloy method, a double alloy method and a diffusion method. The NdFeB substrate can be commercially available or can be prepared according to a conventional method in the art, for example, the raw material composition is subjected to smelting, hydrogen cracking, air flow grinding, pressing and sintering to obtain a blank, and the blank is then mechanically processed and cleaned to obtain the NdFeB substrate; the blank is preferably 52H.

[0031] The raw material composition includes R element, and the R element may be Nd or "Nd and Pr". The content of the R element is preferably 27.5wt%-31.5wt%, for example 28wt%, and the percentage refers to the weight percentage in the raw material composition.

[0032] The raw material composition includes element B, and the content of element B is preferably 0.87wt%-0.99wt%, more preferably 0.94wt%-0.99wt%, and the percentage refers to the weight percentage in the raw material composition.

[0033] The raw material composition may contain Co element, and the content of the Co element is preferably 0-2.5wt%, such as 1wt%, and the percentage refers to the weight percentage in the raw material composition.

[0034] The raw material composition may contain Cu element, and the content of the Cu element is preferably 0.1wt%-0.3wt%, for example 0.2wt%, and the percentage refers to the weight percentage in the raw material composition.

[0035] The raw material composition may contain Al element, and the content of the Al element is preferably 0-0.2 wt %, such as 0.1 wt %, and the percentage refers to the weight percentage in the raw material composition.

[0036] The raw material composition may contain Ga element, and the content of Ga element is preferably 0.1wt%-0.3wt%, more preferably 0.2-0.3wt%, and the percentage refers to the weight percentage in the raw material composition.

[0037] The raw material composition contains T element, and the T element may be one or more of Zn, Si, Ti, V, Cr, Mn, Ni, Ge, Zr, Ti, Nb, Mo, Pd, Ag, Cd, Sb, Hf, Ta, W, O, C, N, S, F and P, preferably Ti and / or Zr; the content of the T element is preferably 0.1wt%-0.25wt%, for example, 0.2wt%, and the percentage refers to the weight percentage in the raw material composition.

[0038] The raw material composition may include M, and the mass percentage of M is preferably 0.1wt%-3.0wt%, and the percentage refers to the weight percentage in the easily demagnetized area; the M is preferably selected from at least one of Al, Co, Cu, Ga, Sn, Pb and In.

[0039] The raw material composition may contain Fe element, and the content of the Fe element is preferably 66wt%-70wt%, where the percentage refers to the weight percentage in the raw material composition.

[0040] Among them, the diffusion method can be conventional in the art, for example: coating a diffusion source on the surface of the substrate of the first magnet or the substrate of the second magnet respectively, and diffusing the heavy rare earth element under heat treatment conditions; the diffusion direction can be parallel to the magnetization direction or perpendicular to the magnetization direction.

[0041] The coating method is preferably a vapor deposition method or a vapor diffusion method.

[0042] Among them, the heat treatment step is preferably performed under vacuum or argon atmosphere at a temperature of 700-950°C for 24-60 hours; then cooled to 200°C, then heated to 400-600°C and kept warm for 1-6 hours, and finally cooled to room temperature to obtain the first magnet or the second magnet.

[0043] The diffusion source used in the diffusion method may be a material type conventional in the art, such as one or more of heavy rare earth metals, heavy rare earth oxides, heavy rare earth hydrofluorides, heavy rare earth fluorides, heavy rare earth hydrogenates, heavy rare earth fluorides, and heavy rare earth-M alloys;

[0044] Preferably, the heavy rare earth in the diffusion source can be selected from at least one of Dy, Tb, Pr, Nd, Ce, Er, Tm, Y, Lu, Gd and Ho; more preferably, Dy and / or Tb; preferably, the M element in the heavy rare earth-M alloy includes one or more of Al, Co, Cu, Ga, Sn, Pb and In elements.

[0045] In some specific embodiments, the Dy content of the easily demagnetized region may be 0-4.3%; for example, 0, 0.85%, 1.6%, 2.6% or 2.9%; the percentage refers to the weight percentage of Dy in the easily demagnetized region. The Dy content refers to the sum of the Dy content in the substrate of the first magnet and the Dy content obtained by diffusion.

[0046] In some specific embodiments, the Dy content of the non-demagnetizable region may be 0-4.0%, such as 0.9%, 1.5%, 1.8% or 2.2%, wherein the percentage refers to the weight percentage of Dy in the non-demagnetizable region. The Dy content refers to the sum of the Dy content in the substrate of the second magnet and the Dy content obtained by diffusion.

[0047] In some specific embodiments, the Tb content of the easily demagnetized region may be 0-1.5%, such as 0 or 0.50%, where the percentage refers to the weight percentage of Tb in the easily demagnetized region. The Tb content refers to the sum of the Tb content in the substrate of the first magnet and the Tb content obtained by diffusion.

[0048] In some specific embodiments, the Tb content of the non-demagnetized region may be 0-1.0%; for example, 0, 0.4%, 0.45% or 0.50%; the percentage refers to the weight percentage of Tb in the non-demagnetized region or the non-demagnetized region. The Tb content refers to the sum of the Tb content in the substrate of the second magnet and the Tb content obtained by diffusion.

[0049] In some specific embodiments, based on the easily demagnetized region, the total content of Dy and Tb may be ≤5%; for example, 0.5%, 1.35%, 2.1%, 2.6% or 3.4%, where the percentage refers to the total weight of Dy and Tb as a percentage of the weight of the easily demagnetized region. The content of Dy and Tb refers to the sum of the content of Dy and Tb in the substrate of the first magnet and the content of Dy and Tb obtained by diffusion.

[0050] In some specific embodiments, based on the non-demagnetization-resistant region, the total content of Dy and Tb may be ≤4.5%; for example, 0.4%, 1.35%, 1.5%, 1.8% or 2.7%, where the percentage refers to the total weight of Dy and Tb as a percentage of the weight of the non-demagnetization-resistant region. The content of Dy and Tb refers to the sum of the content of Dy and Tb in the substrate of the second magnet and the content of Dy and Tb obtained by diffusion.

[0051] In some specific embodiments, based on the NdFeB magnet material, the total content of Dy and Tb may be ≤9.5%; for example, 0.9%, 2.85%, 3.45%, 4.4% or 6.1%; the percentage refers to the total weight of Dy and Tb in the weight percentage of the NdFeB magnet material. Wherein, the content of Dy and Tb refers to the sum of the content of Dy and Tb in the substrate of the first magnet and the second magnet and the content of Dy and Tb obtained by diffusion.

[0052] In some embodiments, when the diffusion source is a heavy rare earth-M alloy, the content of M element is preferably 2wt%-30wt%, and the content of heavy rare earth is preferably 70wt%-98wt%, and the percentage refers to the weight percentage in the diffusion source.

[0053] In the present invention, the total rare earth element content in the first magnet or the second magnet is preferably 28wt%-32.5wt%, more preferably 29.5wt%-31.5wt%, where the percentage refers to the weight percentage in the first magnet or the second magnet; the rare earth element is preferably selected from at least one of Dy, Tb, Pr, Nd, Ce, Er, Tm, Y, Lu, Gd and Ho.

[0054] In some specific embodiments, the easily demagnetized area includes the following components in weight fractions: 7% Nd; 21% Pr; 0.85% Dy; 0.5% Tb; 1.5% Gd; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe; the non-easily demagnetized area includes the following components in weight fractions: 7% Nd; 21% Pr; 1.50% Dy; 1.5% Gd; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe.

[0055] In some specific embodiments, the easily demagnetized area includes the following components in weight fractions: 6.45% Nd; 19.35% Pr; 2.9% Dy; 0.5% Tb; 1.5% Gd; 0.2% Cu; 0.10% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the remainder Fe; the non-easily demagnetized area includes the following components in weight fractions: 6.45% Nd; 19.35% Pr; 2.2% Dy; 0.5% Tb; 2.2% Gd; 0.2% Cu; 0.10% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the remainder Fe.

[0056] In some specific embodiments, the easily demagnetized area includes the following components in weight fractions: 7% Nd; 21% Pr; 1.6% Dy; 0.5% Tb; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe; the non-easily demagnetized area includes the following components in weight fractions: 7.38% Nd; 22.13% Pr; 0.9% Dy; 0.45% Tb; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe.

[0057] In some specific embodiments, the easily demagnetized zone includes the following components in weight fractions: 7% Nd; 21% Pr; 0.5% Tb; 3% Gd; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe; the non-easily demagnetized zone includes the following components in weight fractions: 7% Nd; 21% Pr; 0.4% Tb; 3% Gd; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe.

[0058] In some specific embodiments, the easily demagnetized zone includes the following components in weight fractions: 6.75% Nd; 20.25% Pr; 2.6% Dy; 1.5% Gd; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe; the non-easily demagnetized zone includes the following components in weight fractions: 6.75% Nd; 21% Pr; 1.8% Dy; 2.3% Gd; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe.

[0059] The present invention also provides a neodymium iron boron magnet prepared by the above-mentioned preparation method.

[0060] The present invention also provides an application of the above-mentioned NdFeB magnet in magnetic steel.

[0061] In some specific embodiments, when the mass of a single piece of the magnetic steel is 5-30 g, the width of the bonding area may be 0.05-0.12 mm; and the volume of the bonding area may be 0.5-2% of the total volume of the magnetic steel.

[0062] In the present invention, when the NdFeB magnet is applied to magnetic steel, in order to prevent the high temperature of the easy demagnetization area and the coverage of the reverse magnetic field domain from affecting the non-easy demagnetization area, the width of the easy demagnetization area can be increased by 0.5 mm based on the theoretical easy demagnetization area.

[0063] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0064] The reagents and raw materials used in the present invention are commercially available.

[0065] The positive and progressive effects of the present invention are:

[0066] The NdFeB magnet material provided by the present invention has the same anti-demagnetization capability as the prior art under the condition of lower heavy rare earth cost.

[0067] In a preferred embodiment, when the volume proportion of the easily demagnetized area is 32% and is close to the demagnetization rate of the entire magnetic steel, no obvious demagnetization occurs, but the cost is greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 Schematic diagram of the structure of the NdFeB magnet obtained in Examples 1-10 (1 is the easily demagnetized area, where a=3-4mm; b=17.25mm; c=3.8mm; 2 is the non-easy demagnetized area, where d=11mm; 3 is the bonding area, whose width is 0.05-0.12mm).

[0069] Figure 2 Schematic diagram of the structure of the NdFeB magnet of the present invention (1 is the easily demagnetized area, where a=3-4mm; b=17.25mm; c=3.8mm; 2 is the non-easy demagnetized area, where d1=5.5mm, d2=5.5mm; 3 is the bonding area, whose width is 0.05-0.12mm) DETAILED DESCRIPTION

[0070] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0071] The NdFeB magnet of the present invention is obtained by bonding a first magnet and a second magnet having different coercive forces. The non-demagnetization region can be a magnet, and the structural diagram is as shown in FIG. Figure 1As shown; the non-demagnetization zone may also include two second magnets, the structural schematic diagram is as shown Figure 2 The coercive force of the non-demagnetization zone is 87%-96% of the coercive force of the demagnetization zone.

[0072] In the structure of the NdFeB magnet material obtained in Example 1-10, the easily demagnetized area includes two first magnets, and the non-easy demagnetized area includes one second magnet. The structural schematic diagram is shown in FIG. Figure 1 shown.

[0073] The preparation method of NdFeB magnet material is as follows:

[0074] (1) Melting and casting process: According to the formula shown in Table 1, the prepared raw materials were placed in an alumina crucible and heated in a high-frequency vacuum induction melting furnace at 5×10 -2 Vacuum melting was performed at a temperature below 1550°C in a vacuum of 1000 Pa. Ar gas was introduced into the melting furnace after vacuum melting to a pressure of 30 kPa, and casting was performed at 10 2 ℃ / sec~10 4 The rapidly cooled alloy was obtained at a cooling rate of 1.5 °C / s.

[0075] (2) Hydrogen pulverization process: The melting furnace containing the rapidly cooled alloy is evacuated at room temperature, and then 99.9% pure hydrogen is introduced into the hydrogen pulverization furnace, and the hydrogen pressure is maintained at 0.56-0.9 MPa. After sufficient hydrogen absorption, the temperature is increased while evacuating the furnace to fully dehydrogenate, and then the furnace is cooled and the powder after hydrogen pulverization is taken out.

[0076] (3) Fine pulverization step: The powder after hydrogen pulverization is subjected to jet mill pulverization for 3 hours in a nitrogen atmosphere with an oxidizing gas content of 150 ppm or less and a mill chamber pressure of 0.60 MPa to obtain fine powder. The oxidizing gas refers to oxygen or water.

[0077] (4) Add zinc stearate to the powder after being pulverized by the jet mill, the amount of zinc stearate added being 0.08% of the weight of the mixed powder, and then fully mix using a three-dimensional mixer.

[0078] (5) Magnetic field forming process: Using a right-angle orientation magnetic field forming machine, in an orientation magnetic field of 1.6T, at 0.35 ton / cm 2 The powder with zinc stearate added was once formed into a cube with a side length of 25 mm under a molding pressure of 1.3 ton / cm. After the first forming, it was demagnetized in a magnetic field of 0.2 T. In order to prevent the molded body from contacting the air after the first forming, it was sealed and then a secondary forming machine (isostatic pressing machine) was used to press the molded body at 1.3 ton / cm 2 Secondary forming is carried out under pressure.

[0079] (6) Sintering process: Each formed body is moved to a sintering furnace for sintering at 5×10 -3 Pa, maintained at 300°C, 600°C and 920°C for 1 hour each, and then sintered at 1050-1095°C for 4 hours. Then, Ar gas was introduced to make the gas pressure reach 0.1MPa, and then taken out after cooling to room temperature.

[0080] (7) Grain boundary diffusion: The sintered body is processed into corresponding square sheets and magnets with a sheet thickness of less than 6 mm. The thickness direction is the magnetic field orientation direction. After the surface is cleaned, the raw material prepared with the diffusion source is sprayed on the magnet. The coated magnet is dried, and a coating with a diffusion source is sprayed on the magnet surface in a high-purity Ar gas atmosphere. The magnet is diffused and heat treated at a temperature of 700-950°C for 24-60h. The magnet is cooled to 200°C, then heated to 400-600°C, and kept warm for 1-6h, and finally cooled to room temperature to obtain the desired magnet.

[0081] The raw material compositions of the NdFeB magnet materials in Examples 1-5 and Comparative Examples 1-5 are shown in Table 1 below; the process conditions of the grain boundary diffusion treatment are shown in Table 2.

[0082] Table 1 Magnet components in each corresponding area

[0083]

[0084]

[0085] Table 2

[0086]

[0087]

[0088] The only difference between Example 6 and Example 1 is that the volume proportion of the easily demagnetized area is 50%.

[0089] The only difference between Example 7 and Example 2 is that the volume proportion of the easily demagnetized area is 50%.

[0090] The only difference between Example 8 and Example 3 is that the volume proportion of the easily demagnetized area is 50%.

[0091] The only difference between Example 9 and Example 4 is that the volume proportion of the easily demagnetized area is 50%.

[0092] The only difference between Example 10 and Example 5 is that the volume proportion of the easily demagnetized area is 50%.

[0093] The only difference between Comparative Example 6 and Example 1 is that the volume proportion of the easily demagnetized region is 5%.

[0094] The only difference between Comparative Example 7 and Example 2 is that the volume proportion of the easily demagnetized region is 5%.

[0095] The only difference between Comparative Example 8 and Example 3 is that the volume proportion of the easily demagnetized area is 5%.

[0096] The only difference between Comparative Example 9 and Example 4 is that the volume proportion of the easily demagnetized region is 5%.

[0097] The only difference between Comparative Example 10 and Example 5 is that the volume proportion of the easily demagnetized region is 5%.

[0098] Table 3

[0099]

[0100] Effect Example

[0101] 1. Test method of demagnetization rate

[0102] Demagnetization rate test of no-load back electromotive force before and after demagnetization at 13000rpm@160℃ or 180℃:

[0103] Using an electromagnetic simulation software, the input speed is 13000rmp, and then the temperature is adjusted to 160℃ or 180℃. At the same time, the back electromotive force data of the motor is collected and the changes in the magnetic steel cloud map are observed to determine whether the magnetic steel is demagnetized.

[0104] Among them, Examples 1, 3-6, 8-10 and Comparative Examples 1, 3-6, 8-10 are according to Figure 1 Bonding was performed as shown and the test was performed at 160°C;

[0105] Example 2, Example 7 and Comparative Example 2, Comparative Example 7 are according to Figure 1 The bonding was performed as shown and the test was performed at 180°C. The test results are shown in Table 3.

[0106] 2. Test methods for remanence and coercivity

[0107] The magnetic properties of the NdFeB magnets of Examples 1-5 and Comparative Examples 1-5 were tested using the NIM-10000H BH bulk rare earth permanent magnet nondestructive measurement system of the China Institute of Metrology.

[0108] Easy demagnetization area: Sample preparation specification W2~3±0.1*L17.25±0.1*T3.8±0.1mm, two pieces are stacked for testing, and coils with size W3*L19~20*T2.7mm are used in permanent magnet precision measurement system NIM-62000 for normal and high temperature testing (temperature ≤200℃);

[0109] Non-demagnetization area: Sample preparation specification W7±0.1*L7±0.1*T4±0.1mm, two pieces stacked for testing, using coils with a diameter of 12*T4.2mm in the permanent magnet precision measurement system NIM-62000 for normal and high temperature testing (temperature ≤200℃);

[0110] The test results are shown in Table 2.

[0111] The NdFeB magnet material of the present invention has an easily demagnetized area and a non-easy demagnetized area connected in a bonding form, and the coercive force and proportion of each area are specially designed to achieve remanence, coercive force and anti-demagnetization properties equivalent to those of the prior art, and can greatly reduce the use of rare earths and reduce costs.

[0112] It can be seen from Table 3 that when the volume of the easily demagnetized zone increases to a certain extent, the effect of further increase on the improvement of the demagnetization rate becomes smaller. It can be seen from Example 1, Example 6 and Comparative Example 6 that when the volume of the easily demagnetized zone increases from 5% to 32%, its demagnetization rate decreases from 12.2% to 1.5%, the volume increases by 27%, and the demagnetization rate decreases by 10.7%; when it increases from 32% to 50%, its demagnetization rate decreases from 1.5% to 1.45%, the volume of the easily demagnetized zone increases by 18%, but the demagnetization rate only decreases by 0.5%; other embodiments and comparative examples can also obtain corresponding rules. It can be seen that the coercive force of the easily demagnetized zone is relatively high, and the content of Dy and Tb is high, and its volume share increases, and the cost will also increase; when the volume of the easily demagnetized zone is within the scope of the present invention, it can ensure a demagnetization rate equivalent to that of the prior art while effectively reducing the use of heavy rare earths and saving costs.

[0113] Table 4

[0114]

[0115] The NdFeB magnet material provided by the present invention has a coercive force setting suitable for actual application scenarios and a remanence equivalent to that of the prior art. More importantly, with a lower rare earth metal usage or lower cost, a demagnetization rate equivalent to that of the prior art is obtained, which is lower than 1.8%, and in some preferred implementations can be lower than 1.5%.

[0116] It can be seen from Table 4 that compared with Example 1, the demagnetization rates of Example 1 are comparable to those of Comparative Example 1. However, since the unit price of Dy is RMB 2.55 million / ton and the unit price of Tb metal is RMB 9.05 million / ton, the cost of Tb metal is about 3.55 times or more of the cost of Dy. Under the condition that the total mass of the NdFeB magnet is the same, the content of Tb used in Comparative Example 1 is 0.5% of the total mass of the NdFeB magnet, while the content of Tb in Example 1 is only 0.5% of the mass of the easily demagnetized area in the NdFeB magnet. It can be seen that the amount of Tb used in Example 1 is much lower than that in Comparative Example 1, and its cost is also lower. Therefore, it can be explained that the present invention achieves an effect comparable to that of the prior art at a lower cost. Compared with Comparative Example 2, Example 2 has the same contents of other components except Dy and Tb, and the content of Dy+Tb in Example 2 is 6.1%, while the content of Dy+Tb in Comparative Example 2 is 6.8%. The content of Dy+Tb in Example 2 is less than that in Comparative Example 2, but the demagnetization rate is equivalent to that in Comparative Example 2, which proves that the present invention uses less rare earth metal to achieve the demagnetization rate effect equivalent to that of the prior art, effectively reducing the cost. Compared with Comparative Example 3, Example 4 and Comparative Example 4, and Example 5 and Comparative Example 5, the situation is the same as above, and the NdFeB magnet material of the present invention achieves a good anti-demagnetization effect by using less rare earth metal.

Claims

1. A neodymium iron boron magnet, characterized in that: It includes an easy demagnetization area, a non-easy demagnetization area and a bonding area, wherein the volume of the easy demagnetization area accounts for 15%-50% of the total volume of the NdFeB magnet; Wherein, the volume of the bonding area accounts for 0.5%-4.0% of the total volume of the NdFeB magnet; Wherein, the ratio of the coercive force of the non-demagnetizable region to the coercive force of the demagnetizable region is 0.7-1.

2. The NdFeB magnet according to claim 1, wherein: The volume of the easily demagnetized area accounts for 25%-50% of the total volume of the NdFeB magnet, for example, 32% or 50%; and / or, the ratio of the coercivity of the non-demagnetizable region to the coercivity of the demagnetizable region is 0.87-0.96, preferably 0.90-0.95, for example 0.90, 0.92 or 0.93; And / or, the difference ΔHcj between the coercivity of the non-demagnetizable region and the coercivity of the demagnetizable region is 1 kOe-7.5 kOe, preferably 1 kOe-3 kOe, for example, 1.8 kOe, 2.2 kOe, 2.4 kOe or 2.6 kOe.

3. The NdFeB magnet according to claim 1, wherein: The material of the bonding area is glue, preferably one or more of resin glue, polyester glue and hot melt glue; And / or, the volume of the bonding area is 1%-4%, where the percentage is the percentage of the volume of the bonding area to the total volume of the NdFeB magnet; And / or, the width of the bonding area is 0-0.12 mm, but not 0; preferably 0.05 mm-0.12 mm; And / or, the porosity of the bonding area is 0.

4. A method for preparing a neodymium iron boron magnet, characterized in that: The steps include bonding a first magnet and a second magnet to obtain the NdFeB magnet; Wherein, the first magnet forms an easily demagnetized area; the second magnet forms a non-easy demagnetized area; and the bonding forms a bonding area; Wherein, the volume of the easily demagnetized area accounts for 15%-50% of the total volume of the NdFeB magnet; Wherein, the volume of the bonding area accounts for 0.5%-4.0% of the total volume of the NdFeB magnet; Wherein, the ratio of the coercive force of the non-demagnetization region to the coercive force of the demagnetization region is 0.7-1.

5. The method for preparing a NdFeB magnet according to claim 4, wherein: The width of the bonding area is 0-0.12 mm, but not 0; preferably 0.05 mm-0.12 mm; And / or, the easily demagnetized area includes at least two first magnets, for example, two pieces; And / or, the non-demagnetizable region includes 1-3 pieces of second magnets, such as 1 piece or 2 pieces; and / or, the first magnets are symmetrically distributed on both sides of the second magnet; and / or, the volume of the bonding area accounts for 1-5% of the volume of the easily demagnetized area, preferably 1.58%-3.79%; And / or, the volume of the bonding area accounts for 1-4% of the volume of the non-demagnetizable area, preferably 1.58%-3.79%.

6. The method for preparing a NdFeB magnet according to claim 4, wherein: The preparation method of the first magnet and the second magnet comprises the following steps: treating the NdFeB substrate; the treatment method comprises one or more of a single alloy method, a dual alloy method and a diffusion method; The method for preparing the NdFeB substrate is preferably to obtain a green body by subjecting the raw material composition to smelting, hydrogen cracking, jet milling, pressing and sintering, and then subjecting the green body to mechanical processing and cleaning to obtain the NdFeB substrate; the green body is preferably 52H; Among them, the diffusion method preferably includes the following steps: coating a diffusion source on the surface of the substrate of the first magnet or the substrate of the second magnet respectively, and diffusing the heavy rare earth element under heat treatment conditions; the diffusion direction is parallel to the magnetization direction or perpendicular to the magnetization direction.

7. The method for preparing a NdFeB magnet according to claim 6, wherein: The raw material composition includes an R element, wherein the R element is Nd or "Nd and Pr", and the content of the R element is preferably 27.5wt%-31.5wt%, for example, 28wt%, where the percentage refers to the weight percentage in the raw material composition; And / or, the raw material composition includes element B, the content of element B is preferably 0.87wt%-0.99wt%, more preferably 0.94wt%-0.99wt%, and the percentage refers to the weight percentage in the raw material composition; And / or, the raw material composition includes Co element, and the content of the Co element is preferably 0-2.5wt%, for example, 1wt%, and the percentage refers to the weight percentage in the raw material composition; And / or, the raw material composition includes Cu element, and the content of Cu element is preferably 0.1wt%-0.3wt%, for example 0.2wt%, and the percentage refers to the weight percentage in the raw material composition; And / or, the raw material composition includes Al element, and the content of Al element is preferably 0-0.2wt%, for example, 0.1wt%, and the percentage refers to the weight percentage in the raw material composition; And / or, the raw material composition includes Ga element, and the content of Ga element is preferably 0.1wt%-0.3wt%, more preferably 0.2-0.3wt%, and the percentage refers to the weight percentage in the raw material composition; And / or, the raw material composition includes T element, and the T element is one or more of Zn, Si, Ti, V, Cr, Mn, Ni, Ge, Zr, Ti, Nb, Mo, Pd, Ag, Cd, Sb, Hf, Ta, W, O, C, N, S, F and P, preferably Ti and / or Zr; the content of the T element is preferably 0.1wt%-0.25wt%, for example, 0.2wt%, and the percentage refers to the weight percentage in the raw material composition; And / or, the raw material composition includes Fe element, and the content of the Fe element is preferably 66wt%-70wt%, and the percentage refers to the weight percentage in the raw material composition; And / or, the raw material composition includes M, the mass percentage of M is preferably 0.1wt%-3.0wt%, and the percentage refers to the weight percentage in the easily demagnetized area; M is preferably selected from at least one of Al, Co, Cu, Ga, Sn, Pb and In; And / or, the coating method is a vapor deposition method or a vapor diffusion method; And / or, the heat treatment step is to perform diffusion heat treatment at a temperature of 700-950° C. for 24-60 hours under vacuum or argon atmosphere; then cool to 200° C., then heat to 400-600° C., and keep warm for 1-6 hours, and finally cool to room temperature to obtain the first magnet or the second magnet; And / or, the diffusion source is one or more of heavy rare earth metals, heavy rare earth oxides, heavy rare earth hydrofluorides, heavy rare earth fluorides, heavy rare earth hydrogenates, heavy rare earth fluorides, and heavy rare earth-M alloys; Preferably, the heavy rare earth in the diffusion source is selected from at least one of Dy, Tb, Pr, Nd, Ce, Er, Tm, Y, Lu, Gd and Ho; more preferably, Dy and / or Tb; Preferably, the M element in the heavy rare earth-M alloy includes one or more of Al, Co, Cu, Ga, Sn, Pb and In elements; the content of the M element is preferably 2wt%-30wt%, and the content of the heavy rare earth is preferably 70wt%-98wt%, and the percentage refers to the weight percentage in the heavy rare earth-M alloy.

8. The method for preparing a NdFeB magnet according to claim 6, wherein: The content of Dy in the easily demagnetized area is 0-4.3%; for example, 0, 0.85%, 1.6%, 2.6% or 2.9%; the percentage refers to the weight percentage of Dy in the easily demagnetized area; And / or, the Dy content of the non-demagnetizable region is 0-4.0%; for example, 0.9%, 1.5%, 1.8% or 2.2%; the percentage refers to the weight percentage of Dy in the non-demagnetizable region; And / or, the Tb content of the easily demagnetized region is 0-1.5%; for example, 0 or 0.50%; the percentage refers to the weight percentage of Tb in the easily demagnetized region; And / or, the content of Tb in the non-easily demagnetized region is 0-1.0%; for example, 0, 0.4%, 0.45% or 0.50%; the percentage refers to the weight percentage of Tb in the non-easily demagnetized region or the non-easily demagnetized region; And / or, based on the easily demagnetized region, the total content of Dy and Tb is ≤5%; for example, 0.5%, 1.35%, 2.1%, 2.6% or 3.4%, where the percentage refers to the total weight of Dy and Tb as a percentage of the weight of the easily demagnetized region; And / or, based on the non-demagnetizable region, the total content of Dy and Tb is ≤4.5%; for example, 0.4%, 1.35%, 1.5%, 1.8% or 2.7%, where the percentage refers to the total weight of Dy and Tb as a percentage of the weight of the non-demagnetizable region; And / or, based on the NdFeB magnet material, the total content of Dy and Tb is ≤9.5%; for example, 0.9%, 2.85%, 3.45%, 4.4% or 6.1%; the percentage refers to the total weight of Dy and Tb as a percentage of the weight of the NdFeB magnet material; Alternatively, the easily demagnetized region comprises the following components in weight fractions: 7% Nd; 21% Pr; 0.85% Dy; 0.5% Tb; 1.5% Gd; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe; the non-easily demagnetized region comprises the following components in weight fractions: 7% Nd; 21% Pr; 1.50% Dy; 1.5% Gd; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe; Alternatively, the easily demagnetized region comprises the following components in weight fractions: 6.45% Nd; 19.35% Pr; 2.9% Dy; 0.5% Tb; 1.5% Gd; 0.2% Cu; 0.10% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe; the non-easily demagnetized region comprises the following components in weight fractions: 6.45% Nd; 19.35% Pr; 2.2% Dy; 0.5% Tb; 2.2% Gd; 0.2% Cu; 0.10% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe; Alternatively, the easily demagnetized region comprises the following components in weight fractions: 7% Nd; 21% Pr; 1.6% Dy; 0.5% Tb; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe; the non-easily demagnetized region comprises the following components in weight fractions: 7.38% Nd; 22.13% Pr; 0.9% Dy; 0.45% Tb; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe; Alternatively, the easily demagnetized region comprises the following components in weight fractions: 7% Nd; 21% Pr; 0.5% Tb; 3% Gd; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe; the non-easily demagnetized region comprises the following components in weight fractions: 7% Nd; 21% Pr; 0.4% Tb; 3% Gd; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe; Alternatively, the easily demagnetized region comprises the following components in weight fractions: 6.75% Nd; 20.25% Pr; 2.6% Dy; 1.5% Gd; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe; the non-easily demagnetized region comprises the following components in weight fractions: 6.75% Nd; 21% Pr; 1.8% Dy; 2.3% Gd; 0.2% Cu; 0.03% Al; 0.3% Ga; 0.2% Ti; 0.98% B and the balance Fe.

9. A neodymium iron boron magnet obtained by the preparation method according to any one of claims 4 to 8.

10. Use of the NdFeB magnet according to any one of claims 1 to 4 or 9 in magnetic steel; Preferably, when the mass of a single piece of the magnetic steel is 5-30 g, the width of the bonding area is 0.05-0.12 mm; and the volume of the bonding area is 0.5-2% of the total volume of the magnetic steel.

Citation Information

Patent Citations

  • Gradient distribution neodymium-iron-boron magnet and preparation method thereof

    CN111653407A

  • Composite magnet and motor magnetic assembly

    CN110853862A

  • Neodymium-iron-boron magnet and preparation method and application thereof

    CN111653404A

  • Spliced neodymium-iron-boron magnet with gradient performance and preparation method thereof

    CN116564691A

  • Composite multi-layer NdFeB magnet

    CN201745223U

Cited By

  • Preparation method of neodymium-iron-boron magnet with low demagnetization rate

    CN120473324A

  • Performance-partitioned permanent magnet and preparation method and application thereof

    CN121281959A

  • Performance partitioned permanent magnet and preparation method and application thereof

    CN121281959B